Neurotoxicidade central e periférica induzida por extratos e frações de Manilkara rufula em baratas da espécie Nauphoeta cinerea - Borges , Bruna Trindade (2018)
The Caatinga is an exclusively Brazilian biome, in which the plants are exposed to extreme climatic conditions like low precipitation, elevated temperature, and ultraviolet radiation. The adaptation of plants to these conditions ensures their survival in this biome and results in a unique secondary metabolism. Numerous biological properties are attributed to secondary metabolites, including insecticidal properties. The objective of this dissertation was to evaluate the entomotoxic potential of the crude extract (CEMR) and fractions of the plant Manilkara rufula, native plant of the Caatinga, against cockroaches of the species Nauphoeta cinerea. The locomotor activity of the insects was affected by all concentrations of CEMR, in a dose-dependent manner, leading the animals to lethargy, compromising their exploratory profile. Leg grooming was reduced by all CEMR concentrations tested. In addition, octopamine increased leg grooming, while phentolamine decreased this pattern. Injection of octopamine 15 min before CEMR injection reduced leg grooming, indicating octopaminergic pathway involvement in the observed effects. CEMR induced a negative chronotropic effect, a result like the phentolamine assay, again suggesting the involvement of the octopaminergic pathway in the effects induced by M. rufula. The cholinergic system was also affected by CEMR, which decreased acetylcholinesterase activity. Corroborating with locomotor activity data, CEMR reduced the muscular contraction of the insects. Aiming to identify the compounds responsible for the observed modulations, the aqueous fraction (AFMR) and methanolic fraction (MFMR) were tested in in vivo cockroach metathoracic coxal-adductor nerve-muscle preparation (CNP). MFMR showed little influence on muscle contraction; on the contrary, AFMR reduced the force of contraction. The administration of the fractions in association reduced the muscular contraction like the aqueous fraction alone, suggesting that the saponin, denominated Mi saponin C, the main metabolite of the aqueous fraction, is responsible for the observed effects. Together, the data presented in this dissertation highlight the entomotoxic potential of the M. rufula plant and saponin, the main constituent of the aqueous fraction, which caused significant behavioral, biochemical and electrophysiological alterations, and orchestration of the octopaminergic pathway in these processes.